Evaluation of The Implementation of 4C Skills in Indonesian Subject at Senior High Schools - Selman, Yohanes Fakundo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This research aims to (1) discover to which extent the implementation of the 4C skill reaches its effectiveness and (2) reveal the supporting and inhibiting factors in the implementation of 4C skills in Indonesian subject in all senior high schools throughout Komodo District, West Manggarai Regency. The evaluation model used was the discrepancy evaluation model. The research subjects who participated in this research were two Indonesian teachers and 111 eleventh-graders in Komodo District, West Manggarai Regency. Based on the data analysis, the results reveal that the implementation of 4C skills in Indonesian subject learning in all senior high schools throughout the Komodo District is excellent. Furthermore, it is also revealed the essential factors that support the implementation namely peer support (mutual help), the seriousness of the teacher in providing equal attention to all students, and the ability of teachers to understand and execute the 4C skills learning. Meanwhile, the inhibiting factors found are the lack of textbooks as learning sources and the unconducive classroom situation/ surroundings. To improve the implementation, principals are recommended to (1) conduct regular training and discussion on the implementation of the 4C skills for the teachers, (2) periodically administer evaluation on the learning process to discover the strength and weakness of 4C skills implementation, and (3) improving the learning facilities to support the learning process. For teachers, they are advised to carry out self-assessment/ self-evaluation (assessment for learning) on the implementation of the 4C skills in their classroom.